Nglangkahi Wedding Traditions in Lengkong Village, Bojong District, Tegal City Based on Urf and Sociology Study - Sulistiyowati, Anita (QURU’: Journal of Family Law and Culture, 2023)
Human behavior in choosing a life partner certainly has its own considerations. Sometimes considerations are not just material issues but also immaterial issues. In carrying out a wedding, there is a tradition that is still preserved and guarded by the community, even though this tradition is an unwritten law, it is certain that every region has living traditions that have been in effect for generations. This tradition must be obeyed by the local community because it is manifested in the form of taboos and even traditional ceremonies. Like the unique tradition in Lengkong Village, Bojong District, Tegal City, the people in this village have beliefs and traditions in a wedding which they usually call "nglangkahi Manten". In the research journal the problem formulation will be published, namely: What is the Ngangkahi tradition, How is the ngangkahi tradition practiced, How is the legal sociology review of the ngangkahi tradition. This researcher used field research located in Lengkong Village, Bojong District, Tegal City. The data source was obtained using interview techniques with several community leaders and practitioners of the ngangkati tradition. Which will contain various kinds of information about the Ngangkahi tradition. The factors that influence the existence belief in the prohibition of stepping over are: fanaticism in the teachings of ancestors, the influence of customs and culture, educational factors and the factor of respect for parental advice.